Governing rationalities in children's human rights education. (2020) - Isenström, Lisa; Quennerstedt, Ann
Highlights: Human rights education research was analysed for activated rationalities. 5 governing rationalities in human rights education for children were identified. The rationalities support and contradict each other in complex ways. Governing rationalities connect to differing conceptions of rights for children. Abstract: This research synthesis examines earlier studies within the field of children's human rights in education, with the specific aim of clarifying which rationalities of teaching and learning children's human rights are activated as significant for teachers' thinking and work. Theoretically framed by a Foucauldian governmentality approach, the qualitative analysis identifies five different rationalities in the teaching and learning of children's human rights in previous research. The paper discusses how the identified rationalities support or contradict each other in a complex way and their connection to differing conceptions of rights for children. Further, the possible consequences for teachers, teacher educators and policymakers are considered.